Drive for activity in patients with anorexia nervosa. Issue 1 (29th March 2014) - Sternheim, Lot; Danner, Unna; Adan, Roger; van Elburg, Annemarie
ABSTRACT Objective Hyperactivity and elevated physical activity are both considered symptom characteristics of anorexia nervosa (AN). It has been suggested that a drive for activity (DFA) may underlie these expressions, yet research into DFA in AN remains scant. This study investigated DFA levels in patients with AN and its relation to AN severity. Furthermore, as physical exercise may be a way to reduce negative affect, the influence of negative affect (anxiety) on the role of DFA in AN was tested. Method Two hundred and forty female patients with AN completed measures for DFA, eating disorder (ED) pathology, anxiety, and clinical parameters. Results A strong relation between DFA levels and ED pathology was found, which remained significant even after controlling for negative affect (anxiety). Discussion After much theorizing about DFA in AN this study provides empirical evidence for DFA as a hallmark feature of AN, independent of anxiety levels. Future research should shed light on the relationships between DFA, actual physical activity, and the course of AN. © 2014 Wiley Periodicals, Inc. (Int J Eat Disord 2015; 48:42–45)